Impacts of Population Trends, Agricultural Supply Chains, and Environmental Decline in Otukpo LGA, Benue State, Nigeria - Udoinyang, Nathan (International Journal of Environment, Engineering and Education, 2024)
This research delves into the intricate relationship between population dynamics, agricultural value chain, and environmental degradation in Otukpo Local Government Area (LGA), Benue State, Nigeria. The burgeoning population in the region has precipitated notable shifts in land use patterns, agricultural methodologies, and the overall environmental landscape. A robust research methodology was employed to explore this phenomenon comprehensively. Both primary and secondary data were collected, with a sample size of 400 determined using Taro Yamane's formula. This sample was then strategically distributed among the 13 clans within the LGA, yielding 380 returned samples for meticulous analysis. Statistical analysis, facilitated by tools such as standard deviation and mean, was conducted using SPSS software. Employing a mean criterion of 3.0, questionnaires were administered via survey techniques to discern respondents' perspectives. The research findings illuminate the multifaceted impacts of population dynamics in Otukpo LGA. Notably, these dynamics have instigated challenges within the agricultural value chain, manifesting as farmland degradation and pollution. These repercussions have reverberated throughout the environment, precipitating biodiversity loss, soil contamination, and rampant deforestation. The research also underscores the nuanced nature of these challenges. While population growth undeniably exacerbates these issues, it is crucial to acknowledge the contributory role of ineffective public policies in perpetuating environmental and agricultural dilemmas within the region. In light of these findings, the research advocates for formulating sustainable policies and evidence-based solutions. Addressing these issues holistically demands a concerted effort to mitigate the adverse impacts of population dynamics on agricultural practices and environmental sustainability.